Bioactive glass-ceramic scaffolds by additive manufacturing and sinter-crystallization of fine glass powders. Issue 14 (29th May 2018) - Elsayed, Hamada; Zocca, Andrea; Schmidt, Johanna; Günster, Jens; Colombo, Paolo; Bernardo, Enrico
Abstract: Abstract : Wollastonite (CaSiO3 )–diopside (CaMgSi2 O6 ) glass-ceramic scaffolds have been successfully fabricated using two different additive manufacturing techniques: powder-based 3D printing (3DP) and digital light processing (DLP), coupled with the sinter-crystallization of glass powders with two different compositions. The adopted manufacturing process depended on the balance between viscous flow sintering and crystallization of the glass particles, in turn influenced by the powder size and the sensitivity of CaO–MgO–SiO2 glasses to surface nucleation. 3DP used coarser glass powders and was more appropriate for low temperature firing (800–900 °C), leading to samples with limited crystallization. On the contrary, DLP used finer glass powders, leading to highly crystallized glass-ceramic samples. Despite the differences in manufacturing technology and crystallization, all samples featured very good strength-to-density ratios, which benefit their use for bone tissue engineering applications. The bioactivity of 3D-printed glass-ceramics after immersion in simulated body fluid and the similarities, in terms of ionic releases and hydroxyapatite formation with already validated bioactive glass-ceramics, were preliminarily assessed.